K-pop fandom & sasaeng fans : an exploratory study of hardcore Singaporean fans. - Ho, Samantha Xiang Xin. (2013)
This exploratory study of hardcore Singaporean K-pop fans examines their negotiation of identity vis-à-vis the Korean sasaeng fan discourse. In particular, it seeks to uncover the motivations behind their decisions to travel to Korea to search for K-pop idols, as well as to examine the meaning-making in their consumption and experience of K-pop in Korea. Drawing on data from in-depth interviews and qualitative content analysis of online media texts, I conceive of the crucial role of online media in shaping the perceptions of the masses, in particular the construction of the sasaeng fan identity, thereby influencing the negotiation of identity among hardcore Singapore K-pop fans. Through its findings, this study reveals evident distinctions between the two fan typologies and refutes the hypothesis of hardcore Singaporean K-pop fans becoming sasaeng fans.